RECONCILING NEGATIVITY WITH POSITIVE LEADERSHIP: A PRACTICAL APPLICATION - Lam, Chak Fu; Roussin, Christopher (Journal of Positive Management, 2015)
Purpose: The main goal of this article is to reconcile the concept of negativity with positive leadership approaches in a real-world setting. Methodology: We interviewed Mr. Paul Fayad, ex-President & Chief Executive Officer (CEO) of HHA Services, to describe his experience in implementing positive leadership and the role of negativity, and superficially negative behaviors, in creating an engaged workforce. Findings: Effective positive leadership is not unerringly optimistic in all moments and in all things. Instead, it is a responsibility to create a positive work environment for everyone working in your company. This means that managers have to not only keep their people happy, but also eliminate the negative, which can be the wrong people, the wrong process, the wrong equipment, or other processes that should be eliminated. In the elimination of this negative, sometimes critical (or focused-negative) behaviors are required of the “positive leader”. Implications: Negativity is a part of positive leadership, especially during the hiring process and critical conversation. The importance of addressing negativity is discussed.